Responsive Islamic Education in Exploring Social Values Through the War Takjil Phenomenon: Sociological Perspective in Indonesia - Minhaji, Minhaji; Hosaini, Hosaini; Prasetiyo, Nova Tri; Maktumah, Luluk; Alehirish, Mustafa Hamed Mohamed (Graduate School of UIN Syarif Hidayatullah Jakarta, 2024)
This research aims to explore the social values of Islam reflected in the phenomenon of